O emprego de fermento de pão, Saccharomyces cerevisiae, na síntese de feromônios - Baraldi,Patrícia T. (2004)
The use of pheromones in integrated pest management has been increasing in the last years due to environmental concern. This development is accompanied by the search for simple, efficient and less aggressive synthetic methodologies for the preparation of pheromones. One of these methodologies includes microbiological reactions, more specifically biocatalytic reduction of carbonyl compounds using baker's yeast (Saccharomyces cerevisiae). This review presents the use of baker's yeast as an easy and cheap alternative to obtain enantiomerically enriched compounds employed in the synthesis of pheromones.